An exploratory study of the adoption of artificial intelligence in Burgundy's wine industry. (10th May 2021) - Atwal, Glyn; Bryson, Douglas; Williams, Alistair
Abstract: The objective of this exploratory study is to identify which factors enable or inhibit artificial intelligence adoption within the wine sector and specifically for the Burgundy region. Findings revealed that the winegrower's adoption intention could be assessed according to (a) perceived benefits, (b) organizational readiness, and (c) external pressure.